Painful ophthalmoplegia due to inflammation of the cavernous sinus in a patient with familial Mediterranean fever. Issue 2 (3rd July 2017) - Sato, Mitsuto; Yazaki, Masahide; Miyazaki, Daigo; Kishida, Dai; Nakamura, Akinori; Ikeda, Shu-ichi
Abstract: We report a 32-year-old patient with familial Mediterranean fever (FMV) who presented with painful ophthalmoplegia due to unilateral cavernous sinus inflammation. At age 32, she was admitted to our hospital due to the development of headache, retroorbital pain in the right eye and diplopia. Brain magnetic resonance imaging showed soft tissue thickening with homogenous enhancement at the right cavernous sinus. Hence, a diagnosis of Tolosa–Hunt syndrome was made, and intravenous dexamethasone administration was begun. To date, several inflammatory disorders have been reported to develop in FMF patients, but clinical manifestations in the central nervous system (CNS) other than headache have been rarely seen in FMF patients. Our observations also indicate that Tolosa–Hunt syndrome may be an important CNS complication in FMF patients.